A critical review of EIA follow-up in South Africa: a case study for Gauteng Province - Chigwanhire, Faith (My University, 2021)
Environmental Impact Assessment (EIA) is internationally recognised as a tool for environmental management. When an EIA is done and likely environmental impacts have been identified, recommendations for mitigation against them are made. EIA follow-up (evaluation, monitoring, and communication) to confirm whether these proposed mitigation measures and recommendations are put into practice and whether they have the desired mitigating effect is often not done. While EIA has been legally established in South Africa for the past two decades, there has not been much consideration given to assess implementation of these mitigation measures. This study attempts to address this gap by assessing the extent of implementation of mitigation measures (level of compliance) on seven construction projects executed in different areas within Gauteng Province. Project compliance levels to authorisation conditions and Environmental Management Plan Reports (EMPrs) were used as a base for discussion and the extent to which mitigation measures have been implemented successfully. Perceptions of EIA follow-up participants/project stakeholders, including the Competent Authority, Client (Project Manager) and Environmental Compliance Officer)was also explored to determine their views towards and understanding of EIA follow-up. The findings show that mitigation measures are inadequately implemented and also revealed that EIA follow-up is a neglected element of the EIA process, with several constraints identified. In terms of perceptions over EIA follow-up, all project stakeholder participants acknowledged the value of EIA follow-up in ensuring that mitigating measures are put in place to reduce developmental impacts on the environment by implementing recommendations stipulated in Environmental Authorisations and EMPrs, however several concerns were raised regarding the practice, cost related to implementation of mitigation measures ,inadequate resources in terms of technology and equipment, lack of support and enforcement from competent authorities, inadequate capacity development amongst project stakeholders, poor public participation during EIA process, lack of support from the government through weak regulatory framework, corruption and poor EMP quality. With this, the study has made recommendations that may help to improve EIA follow-up in the context of South Africa
A submitted in partial fulfilment of academic requirements for the Master of Science degree (CW/RR) in the School of Animal, Plant and Environmental Sciences, University of Witwatersrand, 2021